Hidrocarbonetos policíclicos aromáticos em sedimentos de fundo do estuário do rio Potengi, região da grande Natal (RN): implicações ambientais - Queiroz, Maria Sara Maia de (2011)
Estuaries are environments prone to the input of chemical pollutants of various kinds and origins, including polycyclic aromatic hydrocarbons (PAHs). Anthropogenic PAHs may have two possible sources: pyrolytic (with four or more aromatic rings and low degree of alkylation) and petrogenic (with two and three aromatic rings and high degree of alkylation). This study aimed to evaluate the levels, distribution and possible sources of polycyclic aromatic hydrocarbons in the estuary of the Potengi river, Natal, Brazil. Samples of bottom sediments were collected in the final 12 km of the estuary until its mouth to the sea, where the urbanization of the Great Natal is more concentrated. Sampling was performed on 12 cross sections, with three stations each, totaling 36 samples, identified as T1 to T36. The non alkylated and alkylated PAHs were analyzed by gas chromatography coupled to mass spectrometry (GC / MS). PAHs were detected in all 36 stations with total concentration on each varying 174-109407 ng g-1. These values are comparable to those of several estuarine regions worldwide with high anthropogenic influence, suggesting the record of diffuse contamination installed in the estuary. PAHs profiles were similar for most stations. In 32 of the 36 stations, low molecular weight PAHs (with 2 and 3 ring: naphthalene, phenanthrene and their alkylated homologues) prevailed, which ranged from 54% to 100% of the total PAH, indicating that leaks, spills and combustion fuels are the dominant source of PAH pollution in the estuary. The level of contamination by PAHs in most stations suggests that there is potential risk of occasional adverse biological effects, but in some stations adverse impacts on the biota may occur frequently. The diagnostic ratios could differentiate sources of PAHs in sediments of the estuary, which were divided into three groups: petrogenic, pyrolytic and mixing of sources. The urban concentration of the Great Natal and the various industrial activities associated with it can be blamed as potential sources of PAHs in bottom sediments of the estuary studied. The data presented highlight the need to control the causes of existing pollution in the estuary